(untitled) (Fiep Bulletin - online, 2011)
Scoliosis is defined as a twisting of the basic elements of the spine around the vertical axis corresponds to the vital capacity greater air volume mobilized in the mouth between the positions of full inspiration and full expiration. This is an indication of ventilatory reserve. The aim of this study was to investigate the involvement of vital capacity and its relationship with the degree of thoracic scoliosis. Participants were 15 females aged between 18 and 35. Were evaluated by panoramic radiography of the spine and ventilation, this accomplished with the trademark WRIGHT ® spirometer connected to a silicone mask, getting three consecutive measurements, considering the higher value. There was no correlation between degree of scoliosis and impairment of vital capacity, however was found in 47% of cases a substantial impairment of vital capacity on average. It was also observed a moderate correlation between weight change and the ideal vital capacity (r = 0.51), ie the higher the actual weight, the greater the impairment of vital capacity.